Exploring the experiences and perspectives of substitute decision-makers involved in decisions about deceased organ donation: a qualitative study protocol. Issue 12 (23rd December 2019) - Crawshaw, Jacob; Presseau, Justin; van Allen, Zack; Pinheiro Carvalho, Livia; Jordison, Kim; English, Shane; Fergusson, Dean A; Lauzier, Francois; Turgeon, Alexis F; Sarti, Aimee J; Martin, Claudio; D'Aragon, Frédérick; et al.
Abstract : Introduction: In Canada, deceased organ donation provides over 80% of transplanted organs. At the time of death, families, friends or others assume responsibility as substitute decision-makers (SDMs) to consent to organ donation. Despite their central role in this process, little is known about what barriers, enablers and beliefs influence decision-making among SDMs. This study aims to explore the experiences and perspectives of SDMs involved in making decisions around the withdrawal of life-sustaining therapies, end-of-life care and deceased organ donation. Methods and analysis: SDMs of 60 patients admitted to intensive care units will be enrolled for this study. Ten hospitals across five provinces in Canada in a prospective multicentre qualitative cohort study. We will conduct semistructured telephone interviews in English or French with SDMs between 6 and 8 weeks after the patient's death. Our sampling frame will stratify SDMs into three groups: SDMs who were not approached for organ donation; SDMs who were approached and consented to donate and SDMs who were approached but did not consent to donate. We will use two complementary theoretical frameworks—the Common-Sense Self-Regulation Model and the Theoretical Domains Framework— to inform our interview guide. Interview data will be analysed using deductive directed content analysis and inductive thematic analysis. Ethics and dissemination: This study has been approved by the Centre Hospitalier de l'Université de Montréal Research Ethics Board. The findings from this study will help identify key factors affecting substitute decision-making in deceased organ donation, reasons for non-consent and barriers to achieve congruency between SDM and patient wishes. Ultimately, these data will contribute to the development and evaluation of tools and training for healthcare providers to support SDMs in making decisions about organ donation. Trial registration number: NCT03850847 .